An inexpensive system for imaging the contents of multi‐well plates. Issue 12 (4th December 2018) - Bohm, Andrew
Abstract : This paper describes the construction of a low‐cost, open‐source system for imaging the contents of multi‐well plates. Abstract : An inexpensive system for automated imaging of the contents of 12‐, 24‐ and 96‐well plates has been built. The xyz stage is constructed from parts from a light‐duty computer numerical control wood‐carving/engraving machine, and the Arduino‐based board was wired so that it can trigger still images or movies though a microscope‐mounted digital camera. The translation stage provides reproducible three‐dimensional movement of the sample over a volume of 160 mm in x, 100 mm in y and 40 mm in z . A Python script generates the G‐code command file that scans the plate and collects a series of z ‐stacked images of each sample. A second Python script automates the calculation of images with a digitally enhanced depth of field. The imaging system is currently being used to facilitate screening for protein crystals, but it could be used to automate the imaging of many other types of samples in multi‐well plates.